Transportation: Sector Working Paper - World Bank.; McNamara, Robert S. (Washington: World Bank, 1972)
This paper outlines the World Bank's lending, technical assistance and research in the transport sector against the background of previous experience. It discusses the role of transport in overall economic activity, reviews what the Bank has done in support of the sector, and summarizes the general lessons derived from that experience.
The Sector Working Papers have served a useful function at all levels within the Bank; they are therefore being published in a series of pamphlets that deal with the individual sectors in which the Bank is operating.
ne 20/03/2018
Loan
Keywords: Transportation